Genetic breaks caused by ancient forest fragmentation: phylogeography of Staudtia kamerunensis (Myristicaceae) reveals distinct clusters in the Congo Basin - Samuel Vanden Abeele; Katarina Matvijev; Olivier J. Hardy; Dieu-Merci Assumani; Bhély Angoboy Ilondea; Hans Beeckman; Gael U. D. Bouka; Clay Archange Boupoya; Victor Deklerck; Jean-François Flot; Jean-François Gillet; Narcisse Guy Kamdem; et al. (Tree Genetics & Genomes, 2023)
Documenting species and population diversity is becoming increasingly important as the destruction and degradation of natural ecosystems are leading to a worldwide biodiversity loss. Despite the rapid development of genetic tools, many species remain undocumented and little is known about the diversity of individuals and populations, especially for tropical African plants. In this study, we aim to identify putative hidden species and/or differentiated populations in the tropical African tree Staudtia kamerunensis Warb. (Myristicaceae), a widespread species characterized by a high morphological diversity and a complex taxonomical history. Historical herbarium vouchers were sampled and leaf or cambium samples were collected in the field, dried in silica gel, and subsequently genotyped at 14 microsatellite loci (SSRs), as well as sequenced for two nuclear genes ( At103 , Agt1 ) and one plastid region ( psbA-trnH ). These genetic data were then analyzed using Bayesian clustering, population genetics, and the construction of haplowebs to assess genetic clustering patterns, the distribution of genetic diversity, and genetic differentiation among populations. Multiple genetically differentiated clusters were observed in parapatry throughout Central Africa. Genetic diversity was high and similar among these clusters, apart from the most differentiated populations in southeast Democratic Republic of the Congo (DR Congo), which showed lower levels of genetic diversity. The genetic breaks detected between S. kamerunensis populations are likely not indicative of hidden species but rather result from ancient rainforest fragmentation during cold and dry periods in the Pliocene and/or Pleistocene. The strong genetic divergence between populations in southeast DR Congo could be the result of an ongoing speciation linked to ecological niche differentiation.